2023
DOI: 10.1007/s40519-023-01565-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual self-concept, functioning, and practices of women with binge eating episodes

Abstract: Purpose Positive sexuality has received little empirical attention in relation to eating disorders. Two tendencies related to sexuality have been identified among women with anorexia nervosa (avoidance) and bulimia nervosa (disinhibition), but it is unclear if they also apply to women with binge eating episodes without compensatory behaviors. This study aimed at (1) exploring the sexual self-concept, functioning, and practices of women with binge eating episodes with or without comorbid restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…It was found that when there are more binge eating episodes, there are fewer orgasms, sexual function is worse, and sexual dissatisfaction increases [72]. Women with binge eating episodes were generally characterized by poor sexual functioning and a negative sexual self-concept [73]. This statement is supported by the results of a study by Castellini et al [70] with sexually active women, which shows that women with BED and obesity seem to have lower sexual function compared to those without BED and obesity and to controls.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that when there are more binge eating episodes, there are fewer orgasms, sexual function is worse, and sexual dissatisfaction increases [72]. Women with binge eating episodes were generally characterized by poor sexual functioning and a negative sexual self-concept [73]. This statement is supported by the results of a study by Castellini et al [70] with sexually active women, which shows that women with BED and obesity seem to have lower sexual function compared to those without BED and obesity and to controls.…”
Section: Discussionmentioning
confidence: 99%